Effect of body tilt angle on fatigue and EMG activities in lower limbs during cycling - Egana, M.; Ryan, K.; Warmington, S. A.; Green, S. (European Journal of Applied Physiology, 2010)
This study compared the rate of fatigue and lower limb EMG activities during high-intensity constant-load cycling in upright and supine postures. Eleven active males performed seven cycling exercise tests: one upright graded test, four fatigue tests (two upright, two supine) and two EMG tests (one upright, one supine). During the fatigue tests participants initially performed a 10 s all-out effort followed by a constant-load test with 10 s all-out bouts interspersed every minute. The load for the initial two fatigue tests was 80% of the peak power (PP) achieved during the graded test and these continued until failure. The remaining two fatigue tests were performed at 20% PP and were limited to the times achieved during the 80% PP tests. During the EMG tests subjects performed a 10 s all-out effort followed by a constant-load test to failure at 80% PP. Normalised EMG activities (% maximum, NEMG) were assessed in five lower limb muscles. Maximum power and maximum EMG activity prior to each fatigue and EMG test were unaffected by posture. The rate of fatigue at 80% PP was significantly higher during supine compared with upright posture (-68 ± 14 vs. -26 ± 6 W min-1, respectively, P < 0.05) and the divergence of the fatigue responses occurred by the second minute of exercise. NEMG responses were significantly higher in the supine posture by 1-4 min of exercise. Results show that fatigue is significantly greater during supine compared with upright high-intensity cycling and this effect is accompanied by a reduced activation of musculature that is active during cycling.